Disposal behaviour of unused medicines with environmental awareness as moderator: a conceptual paper - Mohd Anuar, Nur Shazrin; Mohamed Abdul Kadir, Juliana; Ismail, Mazida (UiTM Cawangan Johor, 2024)
Rising economies and developing nations lead to expanded access to essential medications. Malaysia is not an exception to the trend of increased pharmaceutical product. They are referred to medications or drugs that are necessary for maintaining public health as well as for the prevention and treatment of illnesses. Pharmaceutical products increased by 24% from 2015 to over 4.5 trillion doses globally in 2020. Nonetheless, not all patients had consumed all the prescribed medicines they have. Unused medicines are defined as pharmaceuticals that are no longer consumed by the intended users or patients. These unused medicines could be improperly disposed. Improper disposal of unused medicines is defined as discarding unused medicine other than returning them to a Medicine Return Programme (NRP). It is shown that most people in Malaysia did not aware of the proper disposition of unused medications. For instance, the potential environmental harm caused by medicines when disposed of in household trash, leading to their presence in landfill and contamination of surface water. Consequently, one objective of this conceptual paper is to examine the factors influencing the disposition behaviour of unused medicines and the moderating effect of environmental converseness in the relationship between intention and disposition behaviour in Malaysia. Health Belief Model (HBM) theory will be used in this paper to explain the factors influencing the disposition behaviour of unused medicines. Quantitative Research Design is used in this study. A sample size of 2,256,108 of Malaysia 's population will be taken for this study. This paper aims to provide a conceptual process for understanding how patients evolve in their disposal behaviour of unused medicines by putting forth a conceptual framework that incorporated these elements. Keywords: Environmental Awareness, Disposal, MRP, Unused Medicine, HBM Theory